Environmental Sustainability in the Shipping Industry: a Synthesis - Hamer, Nis (My University, 2025)
The objective of this work is to establish a holistic overview on sustainability initiatives in the maritime industry. Therefore, the motivation and drivers, why the industry is transitioning are introduced, further does the introduction provide a broad overview on the emissions caused by the maritime transport industry. To establish where researchers suggest improvements in the current policy scheme and abatement pathways two semi-structured literature reviews are conducted. From the structured searches 74 articles and reviews were included, these were supplemented by literature from an unstructured literature search. Predominant theme among the searches is the regulation and abatement of emissions from energy production. These were found to generally be effective, suggestions are made for the expansion of local regulation, better enforcement and monitoring but also the wider improvement of port facilities. The regulation for emissions to water were often found to be regulated insufficiently. Anti-fouling paint particles, under water radiated noise and anchor scouring were found to be widely unregulated. The transition towards greener technologies is often associated with a cost penalty. Which potentially leads to a paradox, in which two different products (sustainable and conventional) compete with each other, yet the company depends both to survive. Another conclusion made is that port and terminal operators should also receive the attention of impact investors. These are key suppliers to the shipping industry and might facilitate the reduction of emissions. This thesis provides an overview on the ongoing transition towards an industry with less environmental impact. It employs a holistic perspective and identifies interconnections between emissions, abatement and some commercial aspects.
Keywords: shipping; maritime transport; regulatory gaps; emission reduction; corporate social responsibility